Association between endoscopist adenoma detection rate and serrated polyp detection: Retrospective analysis of over 200,000 screening colonoscopies - Penz, Daniela; Pammer, Daniel; Waldmann, Elisabeth; Asaturi, Arno; Szymanska, Aleksrandra; Trauner, Michael; Ferlitsch, Monika (Endoscopy International Open, 2024)
Background and study aims Serrated lesions have been identified as precursor lesions for 20% to 35% of colorectal cancers (CRCs) and may contribute to a significant proportion of interval-cancer. Sessile-serrated-lesions (SSLs), in particular, tend to be flat and located in the proximal colon, making their detection challenging and requiring expertise. It remains unclear whether the detection rate for serrated polyps should be considered as a quality indicator in addition to the adenoma detection rate (ADR). This study sought to assess whether the ADR has an effect on the detection rate for serrated polyps.atients and methods In this retrospective analysis, prospectively collected data from 212,668 screening colonoscopies performed between 2012 and September 2018 were included. Spearman correlation and Whitney-Mann U-test were used to assess the association of ADR and the detection rate of SSLs with (SDR) and without hyperplastic polyps (SPADRs), the sessile serrated detection rate (SSLDR) as well as the clinically relevant serrated detection rate (CRSDR), including all SSLs and traditional serrated adenoma, hyperplastic polyps (HPs) >10 mm anywhere in the colon or HPs > 5 mm proximal to the sigmoid.Results The overall mean ADR was 21.78% (standard deviation [SD] 9.27), SDR 21.08% (SD 11.44), SPADR 2.19% (SD 2.49), and CRSDR was 3.81% (3.40). Significant correlations were found between the ADR and the SDR, SPADR, SSLDR, and CRSDR (rho=0.73 vs. rho=0.51 vs. rho=0.51 vs. rho=0.63; all P <0.001). Endoscopists with a mean ADR ≥25% had significantly higher SDR, SPADR, and CRSDR than endoscopists with a mean ADR <25% (all P <0.001; Mann-Whitney U-Test).Conclusions This study shows that endoscopists with higher ADR detect significantly more serrated lesions than those with a lower ADR.